(untitled) (Revista Contexto & Saúde, 2023)
This study aimed to analyze the prescriptions of a basic health unit (BHU) from the perspective of patient safety. The research corresponded to a cross-sectional study involving prescription analysis, realized in a BHU in the Federal District. The sample analyzed came from prescriptions filed by the pharmacy, from February to July 2019. A sample calculation was performed based on the local average demand for care, resulting in 431 prescriptions to be analyzed. Most of the prescriptions were made to women (69.6%). The average age of patients whose prescriptions were analyzed was 49 years old (± 21), with a higher prevalence of young adults aged 20 to 59 years old (53.4%). Most prescriptions were made by doctors (87.7%), manual (78.9%) and originated in the public service (96.7%). Of the 1208 drugs prescribed, 191 (15.8%) were included in the list of Potentially Hazardous Drugs (PHD) used as the basis for this study or were considered to be at high risk. 147 Potential Drug Interactions (PDI) were found, of which almost 30% were of severe severity. The analyzes contributed to identify that there are flaws in the way that the prescriptions are made, which can have consequences that harm the patient’s safety. In addition, it highlights the importance of analysis from a clinical and care point of view. Furthermore, it confirms that the pharmacist is indispensable to ensure the access and safety of the user with regard to the use of drugs.